The Effects of a Creativity Training Program on Students’ Initial Perceptions of Creativity: The Case Study of Mohamed First University, Morocco - Dihi, Mohamed; Bouamri, Abderrahmane (Arab World English Journal, 2018)
Incorporating creativity in education is widely accepted to be a necessity in today's rapidly changing world.However, in the case of Moroccan educational settings, it is noticed that schools continue to be characterized by traditional and conventional instruction.It is true that some students excel in traditional teaching delivery; however, creative learners are neglected and at risk of being rejected.Understanding the nature of creativity and putting it into action are of paramount importance for students to pursue creative opportunities in their own life.This study aims at (1) assessing 22 Moroccan Master's students' general perceptions and attitudes towards creativity; (2) improving students' creativity by introducing them to a list of creativity techniques; (3) evaluating how effectively the proposed creativity training workshops have influenced students' initial views of creativity.The study used questionnaire inquiry data analysis to collect both quantitative and qualitative data.The findings reveal that students hold positive attitudes towards creativity in education.More importantly, the study shows how the proposed creativity training workshops have positively affected students' initial perceptions and attitudes towards creativity.
openalex: W2808241542 mag: 2808241542
Keywords: openalex:import

The Effects of a Creativity Training Program on Students’ Initial Perceptions of Creativity: The Case Study of Mohamed First University, Morocco - Journal, Arab World English; DIHI, Mohamed; BOUAMRI, Abderrahmane (2018)
Incorporating creativity in education is widely accepted to be a necessity in today's rapidly changing world. However, in the case of Moroccan educational settings, it is noticed that schools continue to be characterized by traditional and conventional instruction. It is true that some students excel in traditional teaching delivery; however, creative learners are neglected and at risk of being rejected. Understanding the nature of creativity and putting it into action are of paramount importance for students to pursue creative opportunities in their own life. This study aims at (1) assessing 22 Moroccan Master’s students’ general perceptions and attitudes towards creativity; (2) improving students’ creativity by introducing them to a list of creativity techniques; (3) evaluating how effectively the proposed creativity training workshops have influenced students’ initial views of creativity. The study used questionnaire inquiry data analysis to collect both quantitative and qualitative data. The findings reveal that students hold positive attitudes towards creativity in education. More importantly, the study shows how the proposed creativity training workshops have positively affected students’ initial perceptions and attitudes towards creativity.
openalex: W4237964727
Keywords: openalex:import

The Effects of a Creativity Training Program on Students’ Initial Perceptions of Creativity: The Case Study of Mohamed First University, Morocco - Journal, Arab World English; DIHI, Mohamed; BOUAMRI, Abderrahmane (2018)
Incorporating creativity in education is widely accepted to be a necessity in today's rapidly changing world. However, in the case of Moroccan educational settings, it is noticed that schools continue to be characterized by traditional and conventional instruction. It is true that some students excel in traditional teaching delivery; however, creative learners are neglected and at risk of being rejected. Understanding the nature of creativity and putting it into action are of paramount importance for students to pursue creative opportunities in their own life. This study aims at (1) assessing 22 Moroccan Master’s students’ general perceptions and attitudes towards creativity; (2) improving students’ creativity by introducing them to a list of creativity techniques; (3) evaluating how effectively the proposed creativity training workshops have influenced students’ initial views of creativity. The study used questionnaire inquiry data analysis to collect both quantitative and qualitative data. The findings reveal that students hold positive attitudes towards creativity in education. More importantly, the study shows how the proposed creativity training workshops have positively affected students’ initial perceptions and attitudes towards creativity.
openalex: W4237964727
Keywords: openalex:import